Education on cardiac risk and CPR in cardiology clinic waiting rooms: a randomised clinical trial. Issue 20 (21st July 2021) - McIntyre, Daniel; Thiagalingam, Aravinda; Klimis, Harry; Von Huben, Amy; Marschner, Simone; Chow, Clara K
Abstract : Objective: Waiting time is inevitable during cardiovascular (CV) care. This study examines whether waiting room-based CV education could complement CV care. Methods: A 2:1 randomised clinical trial of patients in waiting rooms of hospital cardiology clinics. Intervention participants received a series of tablet-delivered CV educational videos and were randomised 1:1 to receive another video on cardiopulmonary resuscitation (CPR) or no extra video. Control received usual care. The primary outcome was the proportion of participants reporting high motivation to improve CV risk-modifying behaviours (physical activity, diet and blood pressure monitoring) post-clinic. Secondary outcomes: clinic satisfaction, CV lifestyle risk factors (RFs) and confidence to perform CPR. Assessors were blinded to treatment allocation. Results: Among 514 screened, 330 were randomised (n=220 intervention, n=110 control) between December 2018 and March 2020, mean age 53.8 (SD 15.2), 55.2% male. Post-clinic, more intervention participants reported high motivation to improve CV risk-modifying behaviours: 29.6% (64/216) versus 18.7% (20/107), relative risk (RR) 1.63 (95% CI 1.04 to 2.55). Intervention participants reported higher clinic satisfaction RR: 2.19 (95% CI 1.45 to 3.33). Participants that received the CPR video (n=110) reported greater confidence to perform CPR, RR 1.61 (95% CI 1.20 to 2.16). Overall, the proportion of participants reporting optimal CV RFs increased between baseline and 30-day follow-up (16.1% vs 24.8%, OR=2.44 (95% CI 1.38 to 4.49)), but there was no significant between-group difference at 30 days. Conclusion: CV education delivery in the waiting room is a scalable concept and may be beneficial to CV care. Larger studies could explore its impact on clinical outcomes. Trial registration number: ANZCTR12618001725257.